2018
DOI: 10.1038/s41598-018-35999-9
|View full text |Cite
|
Sign up to set email alerts
|

Sleep selectively stabilizes contextual aspects of negative memories

Abstract: Sleep and emotion are both powerful modulators of the long-term stability of episodic memories, but precisely how these factors interact remains unresolved. We assessed changes in item recognition, contextual memory, and affective tone for negative and neutral memories across a 12 h interval containing sleep or wakefulness in 71 human volunteers. Our data indicate a sleep-dependent stabilization of negative contextual memories, in a way not seen for neutral memories, item recognition, or across wakefulness. Fu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 65 publications
(100 reference statements)
1
12
0
Order By: Relevance
“…Furthermore, while memories are consolidated during sleep, research suggests that sleep attenuates the affective tones of emotional memories (Cox et al, 2018;Cunningham et al, 2014). Supporting this theoretical account, research has found that post-trauma sleep (versus staying awake) led to fewer and less distressful involuntary intrusions (Kleim et al, 2016;Porcheret et al, 2019;Woud et al, 2018).…”
mentioning
confidence: 94%
See 3 more Smart Citations
“…Furthermore, while memories are consolidated during sleep, research suggests that sleep attenuates the affective tones of emotional memories (Cox et al, 2018;Cunningham et al, 2014). Supporting this theoretical account, research has found that post-trauma sleep (versus staying awake) led to fewer and less distressful involuntary intrusions (Kleim et al, 2016;Porcheret et al, 2019;Woud et al, 2018).…”
mentioning
confidence: 94%
“…Indeed, mounting evidences suggest sleep preferentially consolidates emotional memories and makes them long‐lasting (Cox et al., 2018; Hu et al., 2006; Wagner et al., 2001). Besides memories, a few studies suggested sleep may also preserve affective tones of emotional memories, indicated by subjective and physiological responses (Ashton et al., 2019; Baran et al., 2012; Menz et al., 2013; but also see Cox et al., 2018; Cunningham et al., 2014; Van Der Helm et al., 2011 for discrepant findings). Accordingly, one tenable hypothesis is that sleep deprivation in the early aftermath of trauma may alleviate PTSD symptoms, including involuntary intrusions and emotional hyperarousal.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Restorative, or recuperative theories hypothesize that sleep serves one or more of the following functions: to rest and repair [13,14]; to consolidate what we have learned while we were awake [7,15,16,17,18]; to dream [19]; to enhance the immune response [15,19,20,21]; to avoid the serious detrimental effects of deprivation [1,4,9,22]; to detoxify [23].…”
mentioning
confidence: 99%